Effect of telephone contact on further suicide attempts in patients discharged from an emergency department: randomised controlled study. Issue 7552 (25th May 2006) - Vaiva, Guillaume; Vaiva, Guillaume; Ducrocq, François; Meyer, Philippe; Mathieu, Daniel; Philippe, Alain; Libersa, Christian; Goudemand, Michel
Abstract: Objective To determine the effects over one year of contacting patients by telephone one month or three months after being discharged from an emergency department for deliberate self poisoning compared with usual treatment. Design Multicentre, randomised controlled trial. Setting 13 emergency departments in the north of France. Participants 605 people discharged from an emergency department after attempted suicide by deliberate self poisoning. Intervention The intervention consisted of contacting patients by telephone at one month or three months after discharge from an emergency department for attempted suicide to evaluate the success of recommended treatment or to adjust treatment. Control patients received treatment as usual, in most cases referral back to their general practitioner. Main outcome measures The primary outcome measures were proportion of participants who reattempted suicide, number of deaths by suicide, and losses to follow-up at 13 months' follow-up. Secondary outcome measures were types and number of contacts with health care. Results On an intention to treat basis, the three groups did not differ significantly for further suicide attempts, deaths by suicide, or losses to follow-up: contact at one month (intervention 23% (34/147) v controls 30% (93/312), difference 7%, 95% confidence interval − 2% to 15%), three months (25% (36/146) v 30%, difference 5%, − 4% to 14%). Participants contacted at one month were less likely at follow-up to report having reattempted suicide (12% v 22% in control group, difference 10%, 2% to 18%). Conclusion Contacting people by telephone one month after being discharged from an emergency department for deliberate self poisoning may help reduce the number of reattempted suicides over one year.